A Systematic Literature Review on the Effectiveness of Digital Virtual Tour Media in Enhancing Students' Critical Thinking Skills - Purnawan, Widhia; Purrnawan, Widhia (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Critical thinking skills have become an essential competency in modern education; however, the use of traditional instructional media has proven to be less effective in fostering these skills. This study aims to comprehensively evaluate the effectiveness of digital media in the form of virtual tours in enhancing students' critical thinking abilities through a systematic literature review. Following PRISMA guidelines, this review analyzes 20 selected scholarly articles published between 2019 and 2024. 161 The articles examined include the implementation of virtual tour media such as Virtual Field Trips (VFT) and digital museums across various educational levels. The article selection and data extraction processes were conducted systematically and independently by two reviewers, with both quantitative and qualitative synthesis of results. The findings indicate that digital virtual tour media consistently and effectively enhance students' critical thinking skills, particularly in the areas of analysis, evaluation, and inference. The study found that quasi-experimental and developmental research approaches were the most dominant, with the majority of study subjects at the elementary and secondary education levels. The most frequently used instructional models in combination with virtual tours were Problem-Based Learning (PBL), guided inquiry, and Project-Based Learning. This review offers significant scholarly contributions for educators, researchers, and curriculum developers in implementing effective digital virtual tour media to optimize students' critical thinking abilities.